Need Assessment of Physics Learning Evaluation Course on COVID-19 Pandemic Era in Bloom's Taxonomy Topic - Mukhayyarotin Niswati Rodliyatul Jauhariyah; Wasis Wasis; Titin Sunarti; Woro Setyarsih; Abu Zainuddin; Samsul Hidayat (Universitas Lambung Mangkurat, 2021)
Needs assessment aims to understand the requirements of learning in the COVID-19 pandemic era, the use of online learning platforms, the constraints and solutions offered, the